Study of Stream Bank Erosion in Kenagarian Padang Tarok Village Kamang Baru District Sijunjung Region - INDRAYATI, TITI; Edial, Helfia; Farid, Farida (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ Â This study aims to analyze the level of danger of the Kuantan Riverâs stream bank erosion in Padang Tarok Village Kamang Baru District Sijunjung Region based on the flow velocity, slope, soil texture, surface edge of river bank protection and rooting depth ratio. This research is descriptive quantitative data source is primary data collected directly in the field, while secondary data is a source of reference and analysis obtained from the library or related institution. The unit is an area of research that is still visible by river scour abandoned and is still on the river bank, which is controlled by the use of the land with the assumption that the use of the same land, the same slope class characteristics and rate of change in river flow due to river bank erosion will be different or the same. The data analysis is performed measurements and observations in the field and generate primary data into the data analysis on the basis of this study. The results of the study explained: (1) The flow rate varied research areas, not later than 0,94 m/sec and the fastest 0,77 m/sec, (2) Class slope slope areas classified as class II studies, including in the category class slopes and ramps III, including in the category somewhat steep, (3) soil texture in the study area consists of a smooth, somewhat rough and coarse, (4) Protection of the cliff face at the Kuantan River flows quite well so as to prevent erosion, but there is quite critical, because there is no protection of the cliff face that is not able to withstand the riverbank erosion, (5) the ratio of the depth of the root of the high cliffs on the research area of < 10 % and this condition means that the ratio of the depth of the roots of river bank erosion potential at the Kuantan river basin because it is not able to withstand riverbank erosion and ( 6 ) The level of danger Kuantan river bank erosion in Padang Tarok Village Kamang Baru District Sijunjung Region classified as moderate and high for the study sample.Â